PENAMBAHAN EKSTAK BAYAM HIJAU (Amaranthus Hybridus L.) TERHADAP SIFAT ORGANOLEPTIK SOSIS DAGING AYAM - Supranoto, Supranoto; Alfiyan, Riski; Sulistyaningtyas, Sulistyaningtyas; Sukmaningsih, Tri; Viastika, Yanita Mutiaraning (Jurnal Peternakan (Jurnal of Animal Science), 2023)
The research aims to evaluate the effect of adding green spinach extract to broiler chicken sausages in terms of organoleptic properties, namely color and taste. The research used an experimental method with a completely randomized design (CRD) with a 4 x 5 unidirectional pattern. The treatments given bijau spinach extract were: P0: 750 g meat without green spinach extract + 200 g flour; P1: 750 grams of meat + 35 ml green spinach extract + 200 g flour; P2: 750 grams of meat + 45 ml green spinach extract + 200 g flour; and P3: 750 grams of meat + 55 ml green spinach extract + 200 g flour. The results showed that the addition of green spinach extract significantly affected the color and taste of broiler meat sausages. The more green spinach extract was added, the more intense the green color of the sausage, and the panelists preferred the color and taste of the sausage with the addition of green spinach extract. The color and taste of broiler meat sausage were highest at P3. The addition of green spinach extract can improve the organoleptic quality of broiler chicken sausage and is preferred.Â